PERLINDUNGAN HUKUM TERHADAP PEMEGANG SERTIFIKAT TANAH BERBASIS ELEKTRONIK (Studi pada Kantor Pertanahan Kota Medan) - Tarigan, Christina Margaretha br; Purba, Hasim; Siregar, Mahmul (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The electronic certificate program still has loopholes for abuse of authority by the government, especially for the general public who do not understand electronic certificates and also the electronic certificate program. Electronic certificates do not fulfill one of the objectives of the law, namely justice, because there are still many areas that have limited internet access. The legal basis for regulating the issuance of electronic-based certificates as the basis for proof of ownership of land rights is regulated in the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 3 of 2023 concerning the Issuance of Electronic Documents in Land Registration Activities which regulates electronic systems, electronic documents, data, databases and electronic signatures. Legal protection for holders of electronic-based land certificates in Medan City in terms of proving electronic land certificates is not a problem because electronic land certificates.Keyword: Legal Protection, Certificates, ElectronicAbstrak: Program sertifikat elektronik masih saja memiliki celah penyalahgunaan kewenangan oleh pemerintah khususnya bagi masyarakat awam yang belum memahami tentang sertifikat elektronik dan juga program sertifikat elektronik. Sertifikat elektronik tidak memenuhi salah satu tujuan hukum yakni keadilan dikarenakan masih banyak daerah yang memiliki akses internet yang terbatas. Dasar hukum pengaturan penerbitan sertifikat berbasis elektronik sebagai dasar atas bukti kepemilikan hak atas tanah diatur dalam Peraturan Menteri Agraria dan Tata Ruang/Kepala Badan Pertanahan Nasional Republik Indonesia Nomor 3 Tahun 2023 Tentang Penerbitan Dokumen Elektronik Dalam Kegiatan Pendaftaran Tanah yang mengatur mengenai sistem elektronik, dokumen elektronik, data, pangkalan data dan tanda tangan elektronik. Perlindungan hukum terhadap pemegang sertifikat tanah berbasis elektronik di Kota Medan dari segi pembuktian sertifikat tanah elektronik tidak menjadi masalah karena sertifikat tanah elektronik.Kata kunci: Perlindungan Hukum, Sertifikat, Elektronik